Zahide Bacı: An Example of Sufi Mysticism from Ottoman Niš - Ranđelović (Serbia), Milan (Bulletin of the Institute of Ethnography SASA, 2018)
The paper presents an analysis of the saga about Zahide Bacı, the legacy from the Sufi folklore which remained preserved as a part of the cultural and historical heritage of Ottoman Niš. The saga abounds with the leitmotifs from the legends and the parables of the holy people in Islam whose cults were honored as part of the popular religious tradition not only in the Ottoman Empire, but also in other Muslim countries. Through comparative insight into similar sagas, these leitmotifs are identified and their origins analyzed. In that way, we got better insight in the opus of syncretic elements taken over in this saga from the cultures and religions of the Near and Far East. Key words: Zahide Bacı, dervishes, Ottoman Empire, Niš, Islam, mysticism, Sufism